Magnetic Resonance-Guided Focused Ultrasound Myomectomy: Safety, Efficacy, Subsequent Fertility and Quality-of-Life Improvements, A Systematic Review. (April 2014) - Gizzo, Salvatore; Saccardi, Carlo; Patrelli, Tito Silvio; Ancona, Emanuele; Noventa, Marco; Fagherazzi, Simone; Mozzanega, Bruno; D'Antona, Donato; Nardelli, Giovanni Battista
We performed a systematic review about studies reporting data of myomectomy performed by magnetic resonance-guided focused ultrasound (MRgFUS) technique in order to define its safety, feasibility, indications, complications, and impact on uterine fibroid symptom and health-related quality of life (UFS-QOL) and fertility. Outcomes were considered according to fibroids shrinkage, nonperfused volume (NPV), NPV ratio, and uterine fibroid symptoms assessed with UFS-QOL questionnaire (baseline 3, 4, 6, and 12 months). We analyzed 38 eligible studies reporting outcomes about 2500 patients (mean age 43.67 years). The MRgFUS results a safe, efficient, and cost-effective minimal invasive technique for treatment of uterine fibroids. Increasing experience, device improvements, and availability for a larger number of patients are enhancing the outcomes, while the obstetrical ones should be more extensively explored. The MRgFUS could be considered as a minimal invasive alternative to traditional surgical or radiological procedures for the treatment of symptomatic uterine myomas improving both QOL and subsequent fertility.